Relevance of Islamic Education in The Formation of Student Characters - Muyassaroh, Sita Novia; Khikmah, Amila Noor; Isnaini, Shofia; Nabila, Paulina Anisatin (Journal of Islam and Science, 2020)
Character education is essentially a moral education that is expected to shape a better and more responsible human person. This character education teaches how to think and behave well that helps individuals to live and work together as a family, community, and state, as well as helping them to make responsible decisions. In other words, this character education teaches how to educate children to think smartly, to have a strong character and nature to activate the child's brain usually. Character education refers to religious education titled Akhlaqul Karimah, which aims to encourage the habits and behavior of students. In terms of the religion of Islam to build human nature, we need to follow in the footsteps of the Prophet Muhammad role models of the people. He has a character that must be emulated.